(untitled) (Bangladesh Journal of Livestock Research, 2020)
This study was carried out for a period of 70 days to investigate the comparative advantages of feeding total mixed ration (TMR) over conventional feeding in Red Chittagong cows (RCC). 15 RCC milking cows were divided into 3 treatment groups in a Completely Randomized Design (CRD). Existing feeding was denoted as control group (T0). TMR made with 60% roughage and 40% concentrate in the forms of block (T1) and mash (T2) were provided to other treatment groups. DM and CP intake was significantly (p<0.001) higher in T1 group. Body weight gains were not differed significantly, but better milk yield (p<0.001) and milk components were observed in TMR feeding groups. Except ADF, other nutrient digestibility in TMR group were significantly (p<0.05) better than T0. Total volatile fatty acids (p<0.01) and ammonia-nitrogen (p<0.05) in TMR feeding groups were significantly higher than T0. Considering overall observation, TMR either in block or mash performed better than control. Bangladesh J. of Livestock Res. 21-25: 69-81, 2018